Formulation And Antioxcidant Activity Test Of Clay Mask Extracted Ethanol Tamarillo (Solanum betaceum Cav.) - Yessi Febriani; Sudewi Sudewi; Rosanna Sembiring (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Tamarillo (Solanum betaceum Cav.) is a plant that is spread in Java, Bali and North Sumatra, which is rich in nutrients and contain flavonoid as antioxidants that can prevent cell damage due to oxidative stress. Clay-based face masks have a firming and cleansing effect on the skin. Tamarillo was extracted by maceration method using 96% ethanol extract, phytochemical screening was carried out. Clay mask formulation with extract concentration of 1.5%, 2%, 2.5% and blanks. Physical quality test of clay mask preparations included homogeneity test, stability test, pH test, dry time test, irritation test, effectiveness test of clay mask preparation on volunteers using the Skin Analyzer Checkher (Aram), preference test and antioxidant test using the DPPH method. The results showed that the ethanol extract tamarillo contained alkaloids, flavonoids, saponins and could be formulated into a clay mask preparation that was homogeneous, stable, met the pH requirements, and dried time. The results of the effectiveness test using a checkher skin analyzer give the effect of reducing blemishes, reducing pores, moisturizing, not causing irritation to the skin. The antioxidant activity of the ethanol extract tamarillo were in the moderate category with an IC50 value of 201 g/mL and the clay mask preparation of the ethanol extract tamarillo with a concentration of 2.5% was in the medium category with an IC50 value of 221 g/mL.